Analysis on Allowable Catch Policy for Fisheries Resource Utilization in Pasuruan, East Java - Wildan Alfarizi; Guntur Guntur; Amin Setyo Leksono (Graduate Program, 2016)
Lack of knowledge and information about fisheries activities, particularly the importance of sustainable management for marine fisheries (catching) is the underlying reason why fish resource potential has yet been managed and utilized well. The study is conducted to determine the number of sustainable fishing and the total allowable catches in Pasuruan, East Java. It also aims at describing status of fishery resources utilization and developing strategies for fishery resources management in Pasuruan, East Java. Walter-hilbron method is used to analyze model prediction of the stock and the status of fisheries utilization. Schaefer and Fox methods are used to calculate Maximum Sustainable Yiled (MSY) and Total Allowable Catch (TAC). The analysis was applied using fisheries data from 2004 to 2014. The strategies being developed and analysis towards importance of the strategy are analyzed using Focus Group Discussion (FGD). Based on Fox model, the MSY is 9,419.86 tons and TAC is 7,535.89. Based on the data, fisheries utilization in Pasuruan, East Java is categorized as overexploited. Most respondents in the Focus Group Discussion (81.74%) agree that strategies of fisheries resources utilization in Pasuruan, East Java is the suitable strategy for fishing ground-based fishing operation as well as fishing season management.Keywords: management strategies, overfishing, sustainability, the status of utilization